Investigation of hydrogel membranes containing a combination of timolol maleate and brimonidine tartrate for ocular delivery - Dubey, Mr. Akhilesh (Asian Journal of Pharmaceutics (AJP), 2014)
Hydrogels are comprised of a crossâ€linked network of polymers.Water penetrates these networks, resulting in swelling and giving the hydrogel a soft and rubbery consistency, thereby maintaining the integrity of the membrane. Because of the drawback of conventional therapy for ocular delivery, a hydrogel membrane containing a combination of timolol maleate and brimonidine tartrate were formulated for the treatment of glaucoma. In the present investigation, hydrogel membranes were prepared using polymers like gelatin, PVA and chitosan, which were crossâ€linked using physical and/or chemical methods. The crossâ€linking of the membranes was confirmed by Fourier transform infrared spectroscopy (FTIR), Xâ€ray diffraction (XRD) and Differential scanning calorimetry (DSC) studies. From the scanning electron microscopy (SEM) of the membranes, it appeared homogenous and showed no separation. The pH of the membranes ranged from 7.21â€7.4. The hydrogels showed a considerably good swelling ratio ranging from 91.66â€372.72%. The drug content ranged from 82.78â€95.62%. The in vitro drug release study indicated that there was a slow and sustained release of the drug from the membranes that were sufficiently crossâ€linked and followed zero order release. The Intraocular pressure (IOP) lowering activity of the prepared formulation was compared with the marketed formulation, and it was found that the IOP lowering action was sustained for a long period of time. Stability studies proved that the formulations could be stable when stored at room temperature. Results of the study indicate that it is possible to develop a safe and physiologically effective hydrogel that is patient compliant. Key words: Crossâ€linking, differential scanning calorimetry, fourier transform infrared spectroscopy, glaucoma, hydrogels, scanning electron microscopy, X-ray diffraction